Advances in abrasive technology XIX selected, peer reviewed papers from the 19th International Symposium on Advances in Abrasive Technology, October 2-5, 2016, Stockholm, Sweden - Krajnik, Peter (Materials science forum ;, 2016)
This book will be useful for academics and practicing engineers in advancement of the efficient materials removal technologies for modern mechanical engineering.